2015
DOI: 10.1038/srep08731
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection can affect energy modulating hormones and body weight in germ free mice

Abstract: Helicobacter pylori, is an invariably commensal resident of the gut microbiome associated with gastric ulcer in adults. In addition, these patients also suffered from a low grade inflammation that activates the immune system and thus increased shunting of energy to host defense mechanisms. To assess whether a H. pylori infection could affect growth in early life, we determined the expression levels of selected metabolic gut hormones in germ free (GF) and specific pathogen-free (SPF) mice with and without the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
0
36
0
1
Order By: Relevance
“…3A–C). H. pylori has been reported to influence physiological regulation of metabolic hormones involved in food intake, energy expenditure and body mass (Khosravi et al, 2015). We found that the serum level of gastric inhibitory polypeptide (GIP) and leptin were higher in animals infected with H. pylori when given a normal diet at 12 weeks compared to the non-infected controls, and the level of GIP was further increased in H. pylori -infected group fed HFD compared with HFD controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3A–C). H. pylori has been reported to influence physiological regulation of metabolic hormones involved in food intake, energy expenditure and body mass (Khosravi et al, 2015). We found that the serum level of gastric inhibitory polypeptide (GIP) and leptin were higher in animals infected with H. pylori when given a normal diet at 12 weeks compared to the non-infected controls, and the level of GIP was further increased in H. pylori -infected group fed HFD compared with HFD controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have highlighted that there is an ongoing crosstalk between H. pylori and the gut microbiota which is associated with the gut inflammation (Khosravi et al, 2015). Thus, we investigated whether the aggravating effect of H. pylori on HFD-induced IR is associated with perturbation of the gut microbiota.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increase of GIP in germ free mice was not statistically significant. Thus Hp down-regulated the expression of host GLP-1 or accelerates the degradation of incretins (a class of neuropeptides that represent insulin secretion stimulators) [12]. Both of the peptides are implicated in adequate glucose metabolism by the cells.…”
Section: Pathogenesis Of Metabolic Changes and Pro-inflammatory Statementioning
confidence: 99%
“…The activation of the immune system also elevated levels of leptin (also known as "hunger hormone"), insulin and peptide YY [12].…”
Section: Pathogenesis Of Metabolic Changes and Pro-inflammatory Statementioning
confidence: 99%